Penggunaan Teknologi Tepat Guna Sistem Hidroponik dengan Memanfaatkan Lahan Kosong Di Kelurahan Rembang - Witjaksono, Gideon Setyo Budi; Fachrani, Dhewintha Kusuma; Samodro, Intan Febriana; Hariyono, Salsabilla Prabawati; Arfi, Zanetta Najlaa Putri; Admanegara, Ronnald Christanto (Universitas Gajah Putih, 2023)
One of the problems that existed at the Rembang Village Office was due to the vacant land which was one of the obstacles, the UPNVJ Thematic Community Service students decided to use hydroponics as a planting medium to be developed because it did not require large areas of land, as well as the tools and materials needed to make hydroponics. easy to get and how to make it easy. Mustard greens are one of the easiest plants to grow using hydroponic growing media, so we decided to plant mustard greens because of its ease of cultivation. Compared to existing planting media, hydroponic growing media has better possibilities. So that the planting medium only needs to be fertilized, watered, and occasionally cleaned. In order for the Rembang Village Office to become an example of hydroponic planting for Rembang Village residents, UPNVJ Thematic KKN students established and planted using hydroponic planting materials to optimize this.